An approach to risk-based maintenance strategy of a printing press - Kar, Ajvit; Pal, Arun Kiran (Journal of Print and Media Technology Research, 2023)
The unexpected failures, downtime associated with breakdown and make ready, loss of production and higher maintenance costs are the major problem in any printing press. Risk based maintenance strategy helps in designing an alternative methodology to minimise the risk by identifying the breakdown pattern and then increasing the reliability. Reliability analysis is necessary for every type of machinery for fault detection, risk assessment and evaluation, and maintenance planning. The probability of failures that hinder the reliability can be influenced by some technical, administrative or management actions. The aim of the proposed study is to analyse reliability and availability for maintenance planning on the basis of risk index and overall equipment effectiveness. And maintenance of equipment is prioritized based on the risk which helps in reducing the overall risk of the press.